Constructing Social Memory in Industrialization in Sherwood Anderson’s Poor White - Shu, Qizhi (Pacific International Journal, 2025)
With a story of a small American rural town undergoing industrialization, Sherwood Anderson’s Poor White displays that the small town of Bidwell has lost its individuality and beauty in America’s transformation from a primarily agrarian society into an industrialized nation. The critical concern has always focused on the nostalgia reflected in the social transformation, paying little attention to the formation of industrial social memory. This paper, borrowing Jan Assmann’s illustration of material, spatial and conceptual memories, will try to analyze the construction of industrial social memory in the story. It argues that the story records how industrialization causes significant changes in the life of the small town and the citizens by penetration of mechanical memory, homogenization of spatial memory and embodiment of conceptual memory. It holds that the story reflects in the gradual fading of agricultural material memory, a new mechanical production method replaces the traditional labor-intensive method and transforms traditional labor patterns and rural life into industrial style in which a new social memory, the mechanical memory, is formed. In representing that the rapid industrialization in the small town of Bidwell compels spatial changes with extensive construction of factories, buildings, and railways, Anderson exposes natural and cultural spaces are remodeled and altered along with the country’s industrial development, which constitutes the townspeople’s spatial memory in industrialization. Meanwhile, their self-identity and values are greatly affected by the completion of industrialization. Their consumption concepts and lifestyles have undergone tremendous changes, and their desires for money and profit become increasingly strong. All these result from the materialistic and mechanical ideology that serves as the origin and embodiment of their conceptual memory in industrialization. Anderson’s story manifests that social memory is a dynamic entity undergoing repeated revisions by newly acquired knowledge or expanded cognitive abilities. In this course, it is not the past itself, but the way people modernize the past in relation to the present and to the desired future that matters. Therefore, Anderson finally conveys the idea that real values will survive in the construction of industrial social memory, although he gives a nostalgic glimpse of the social upheaval with struggles between the old and the new versions of social memory.